Model Pengelolaan Konflik di Lembaga Pendidikan Islam - Dina Maulidatul Hasanah; Nur Izsasi Aminah Haryanti; Putri Anadatul Ustazia; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research uses a literature review study method to explore conflict management models in educational institutions, especially Islamic education. Some of the models found include avoiding, accumulating, negotiating, cooperating, and competing. Conflict management involves three stages: identification, assessment, and resolution, with the main key being identification and assessment. The success of conflict management depends on the leader's ability to choose the right strategy, such as deliberation and tahkim. An effective approach involves all relevant parties and can turn conflict into development opportunities. The conclusion emphasizes the importance of understanding conflict in the context of Islamic education and the need to explore conflict management models to improve the quality of educational institutions. This article also discusses various approaches to conflict management, including deliberation, negotiation, fastabiqul khirot, islah, and returning to goals, as well as highlighting the important role of families, schools, and communities in education. Effective conflict management is necessary to transform conflict into development opportunities and support a harmonious educational environment.